The effect of pressure, opportunity, and rationalisation on asset misappropriation in public organisations: Evidence from emerging markets - Ariffin, Nurul Atikah Mohd; Hasnan, Suhaily; Ali, Mazurina Mohd; Harymawan, Iman (Journal of Asian Scientific Research, 2023)
This study aims to analyse the factors affecting asset misappropriation from the Fraud Triangle Theory perspective: pressure, opportunity, and rationalisation. Pressure, the first facet, is dissected into financial and non-financial strains, including the taxing burden of work. To represent opportunity and rationalisation, proxies are utilized-weak internal control mirrors opportunity, while poor organizational culture encapsulates rationalisation. Employees who were chosen as samples are employees with a position or authority to carry out certain tasks. A questionnaire was distributed to 400 respondents, and only 206 questionnaires were returned and processed for analyses in this study. The results of this study indicate that organisational culture significantly influences asset misappropriation incidences in Malaysian public organisations. However, financial pressure, work pressure, and internal control factors do not significantly affect the misappropriation of assets. This study underscores the importance of mitigating asset misappropriation by focusing on curbing employees' negative rationalization. Strengthening internal control measures and ensuring equitable task assignments emerge as crucial strategies. The outcomes contribute to the limited discourse on asset misappropriation, especially in the context of government agencies in emerging markets. As organizations strive to foster a secure environment, addressing cultural aspects and refining internal controls emerge as pivotal avenues for minimizing asset misappropriation risks.